HUBUNGAN ASUPAN SERAT DAN CAIRAN DENGAN KEJADIAN KONSTIPASI PADA IBU PASCA MELAHIRKAN - Muawanah Muawanah; Triska Susila Nindya (Media Gizi Indonesia, 2016)
Postpartum constipation with symptoms such as pain or discomfort, straining and hard stools is a common condition that affects the incidence of hemoroids and pain in the area of episiotomy. Constipation is associated with inadequate intake of fi ber and fl uid. This study aimed to analyze the relationship between intake of fiber, fluids and constipationin postpartum mother. The study design was observational with cross sectional approach on thirty three (33) post partum mothers using systemic random sampling method in April to May 2016. Data was analyzed by chi-square test. The result showed that 97% of postpartum mother had inadequate fi ber intake and only 3% were adequate. There was 9.1% postpartum mother with inadequate fluid intake and 90.9% were categorized as adequate. There was 54.5% of postpartum mother had constipation, while 45.5% not constipated. Based on chi-square test, there was no signifi cant relationship between fiber intake, fluid intake and constipation (p > 0.05). The conclusion that there was no relationshipin fiber intake, fluid intake with the incidence of constipation in postpartum mother. This requires provision of health education to prevent the occurance of constipation in postpartum mother.Keywords: fluid intake, fiber intake, constipation, postpartum